Associated Myocarditis: A Predictive Factor for Response? - Walid Shalata; Nir Peled; Itzhak Gabizon; Omar Abu Saleh; Waleed Kian; Alexander Yakobson (Case Reports in Oncology, 2020)
In the present case report, we aimed to describe 2 cases of myocarditis occurring as serious adverse effects of immune checkpoint inhibitors (ICIs) administered as treatment for metastatic melanoma. We describe 2 female patients: an 81-year-old treated with pembrolizumab and a 55-year-old treated with a combination of nivolumab and ipilimumab. Both patients underwent resection of metastases; while under treatment, both developed myocarditis, most probably as a toxicity from pembrolizumab and nivolumab plus Ipilimumab, respectively. While they achieved complete response, the occurrence of myocarditis as a toxicity of ICIs may have been a predictive sign that the immune system was sufficiently activated by the checkpoint inhibitor therapy to induce complete remission.